Strain and process improvement for kojic acid production by Aspergillus flavus link S44-1 - Prabu, Rajagopalan (2012)
Kojic acid, 2-hydroxy-methyl-5-hydroxy-γ-pyrone, is an organic acid that can be produced in submerged fermentation by Aspergillus spp. Kojic acid has many potential applications in various fields such as cosmetic, medical, food, agriculture and chemical industries. The focus of this study was on the improvement of industrial kojic acid production through strain and process development. The feasibility of using random mutation method for the improvement of kojic acid producing strain, Aspergillus flavus Link S44-1, was performed using N-methyl-N' nitro-Nnitrosoguanidine (NTG), Ultraviolet (UV) and gamma irradiation. For process development, two possible methods for kojic acid production; (i) biotransformation using resuspended cell system, and (ii) enzymatic synthesis using enzymes extracted from cell biomass were studied. The production processes were performed in shake flask and 2 L stirred tank bioreactor using various types of sugar. The enzymes that were relevant to kojic acid synthesis were extracted from cell biomass and assayed for the activities. The effect of various process parameters and conditions such as dissolved oxygen tension (DOT) and carbon source feeding strategies on the activities of enzymes relevant to kojic acid synthesis were also investigated. The performance of kojic acid production methods developed in this study was compared with the conventional fermentation process, in term of yield and productivity. The improved mutants (A. flavus NTG-MTDC-22 and A. flavus UV-MTDC-12 and A.flavus G-MTDC-17) were capable to produce kojic acid up to a final concentration of 46, 42, and 49 g/L using fed-batch fermentation technique respectively. This was almost 2.5 fold higher than those produced by the parent strain. Among the kojic acid relevant enzymes, higher activities of glucose dehydrogenase and gluconate dehydrogenase were detected in mutant strains as compared to the parent strain. This result indicated that these two intracellular enzymes played important roles in the conversion of sugar to kojic acid. Several kojic acid pathways in A. flavus based on the relationship between the activities of enzymes and kojic acid synthesis were identified and proposed. The involvement of glucoside 3-dehydrogenase enzyme, as indicated by the conversion of 3 -keto glucose to kojic acid, was the potential pathway of kojic acid by A. flavus. Production of kojic acid by A. flavus mutant in fed-batch fermentation with glucose feeding was about 2.3 fold higher than conventional batch fermentation. Kojic acid fermentation performance in 2 L stirred tank bioreactor was greatly influenced by the DOT levels in the culture. The highest kojic acid production was obtained when the DOT level was controlled at 60% saturation throughout the fermentation, which was related to high activities of glucose dehydrogenase and gluconate dehydrogenase. Reduced kojic acid production was observed when the DOT was controlled at low levels (20 and 40% saturation) and also at very high level (80%). The mycelia of A. flavus mutant can also be utilised for the biotransformation of various carbon sources to kojic acid. Among the carbon sources tested, high yields (0.4 g/g and 0.37 g/g) were obtained with glucose and sucrose, respectively. Kojic acid can also be synthesised enzymatically using crude enzymes extracted from the mycelia of A. flavus mutant. The enzymatic synthesis using glucose as a carbon source was about 4 and 5 times lower as compared to fed-batch fermentation and biotransformation using resuspended mycelia, respectively. To our knowledge the enzymatic method for kojic acid synthesis has not been reported in the literature. The simple method developed in this study for the improvement of kojic acid producing fungus and the alternative methods for kojic acid production may be applied industrially. This novel process could be useful to produce kojic acid free from pigments and other metabolites , which will make purification steps easier. High quality kojic acid is required for use in pharmaceutic and cosmetic industries. In addition, reduced cost of production is expected with the elimination of complicated purification procedure.